2023
DOI: 10.1001/jamaoncol.2023.1891
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Duration of Immunotherapy and Overall Survival in Advanced Non–Small Cell Lung Cancer

Abstract: ImportanceFor patients with advanced non–small cell lung cancer (NSCLC) treated with frontline immunotherapy-based treatment, the optimal duration of immune checkpoint inhibitor (ICI) treatment is unknown.ObjectiveTo assess practice patterns surrounding ICI treatment discontinuation at 2 years and to evaluate the association of duration of therapy with overall survival in patients who received fixed-duration ICI therapy for 2 years vs those who continued therapy beyond 2 years.Design, Setting, and Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…In addition, we also observed significantly improved OS (17.7 vs. 7.7 vs. 8.9 months) in the Atezo group in compared to other two groups despite small sample size. This discordance between PFS and OS is consistent with previous studies that showed atezolizumab and other ICIs may have delayed anti-tumor effect that lasts beyond treatment period ( 6 , 14 , 15 ). Median PFS correlates poorly with median OS and may underestimate the clinical benefits of immunotherapy ( 16 , 17 ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we also observed significantly improved OS (17.7 vs. 7.7 vs. 8.9 months) in the Atezo group in compared to other two groups despite small sample size. This discordance between PFS and OS is consistent with previous studies that showed atezolizumab and other ICIs may have delayed anti-tumor effect that lasts beyond treatment period ( 6 , 14 , 15 ). Median PFS correlates poorly with median OS and may underestimate the clinical benefits of immunotherapy ( 16 , 17 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, treatment de-escalation in patients who attain a molecular response indicated by ctDNA clearance may reduce the personal and financial burden of overtreatment. Elective immunotherapy discontinuation past 2 years is well supported ( 44–46 ) and proof-of-concept studies have shown that sustained ctDNA clearance may identify candidates for immunotherapy de-escalation ( 47 ); nevertheless, there are currently no molecularly informed approaches to guide treatment de-escalation. Translating these findings to the clinic, early on-therapy ctDNA persistence prior to and independent of the radiographic response can identify patients not attaining therapeutic benefit, who can be rapidly and accurately guided to alternate therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Very few methodical studies have been published on post-treatment longer-term QoL from observational real-world data focusing on immunotherapy as well as on other cancer treatments such as chemotherapy and radiotherapy 1113 16 . Moreover, studies that investigated QoL in this population so far had a follow-up of under one year 17 , while ICI treatment regimens typically have an intended duration of two years 18 . Patients’ QoL may therefore be affected, even long after treatment with ICIs is initiated.…”
Section: Introductionmentioning
confidence: 99%